You shouldn't have come here eaudiobook - Rose, Jeneva (Blackstone Publishing, 2023)
AN INSTANT NEW YORK TIMES BESTSELLER "Everything I want in a thriller. Sexy, shocking, and tense with an ending I never saw coming. Jeneva Rose is the queen of twists."—Colleen Hoover, #1 New York Times bestselling author The highly anticipated new thriller from the New York Times bestselling author of The Perfect Marriage and One of Us Is Dead You've opened up your house and your heart to a total stranger ... What could possibly go wrong? Grace Evans, an overworked New Yorker looking for a total escape from her busy life, books an Airbnb on a ranch in the middle of Wyoming. When she arrives at the idyllic getaway, she's pleased to find that the owner is a handsome man by the name of Calvin Wells—and he's eager to introduce her to his easygoing way of life. But there are things Grace discovers that she's not too pleased about: A lack of cell phone service. A missing woman. And a feeling that something isn't right with the ranch. Despite her uneasiness, the two bond and start to fall for one another. However, as her departure date nears, things change for the worse. What began as a playful romance soon turns into a complicated web of lies. Grace grows wary of Calvin as his infatuation for her seems to have morphed to obsession. Calvin fears that Grace is hiding something from him—including her reason for staying at his ranch to begin with. Vacation flings typically end in heartbreak, but for Grace and Calvin, it'll be far more destructive.